Knowledge Spillovers From Superstar Tech-Firms : The Case of Nokia - Ali-Yrkko, Jyrki (IMF Working Papers; Working Paper, 2021)
Do workers hired from superstar tech-firms contribute to better firm performance? To address this question, we analyze the effects of tacit knowledge spillovers from Nokia in the context of a quasi-natural experiment in Finland, the closure of Nokia's mobile device division in 2014 and the massive labor movement it implied. We apply a two-stage difference-in-differences approach with heterogeneous treatment to estimate the causal effects of hiring former Nokia employees. Our results provide new evidence supporting the positive causal role of former Nokia workers on firm performance. The evidence of the positive spillovers on firms is particularly strong in terms of employment and value added.